Hacking the Akashic Records: The Next Domain for Military Intelligence Operations?. Issue 2 (17th February 2020) - Levin, Jeff
Abstract: This paper outlines a hypothetical six-dimension doctrine for military intelligence-gathering in the Akashic domain. The Akashic records are described by esotericists and mystics as a permanent record of all thoughts, feelings, and actions, stored in a kind of cosmic memory bank outside of space and time. Psychics, clairvoyants, and other intuitives purport to read the records, suggesting that development of an operational strategy for accessing such information may be possible. Command oversight, however, would present significant moral challenges, as "hacking" into this information would be a personally intrusive invasion of privacy with serious repercussions for the operators and state sponsors.